Autoantigen recognition by thyroid-infiltrating T cells in Graves disease. - Dayan, C; Londei, M; Corcoran, A; Grubeck-Loebenstein, B; James, R; Rapoport, B; Feldmann, M (1991)
Graves disease is a common form of human autoimmune thyroiditis. It shares many pathological features and HLA associations with other, less easily studied, organ-specific autoimmune conditions such as insulin-dependent diabetes mellitus, and hence it is also a useful model for understanding these other diseases. We have previously shown that thyroid-infiltrating T cells in Graves disease that have been recently activated in vivo specifically recognize autologous thyroid epithelial cells. However, the autoantigens involved were not defined. In this study, we have made use of antigen-independent T-cell cloning techniques to show that at least three different thyroid antigens, three different epitopes on a single antigen, and two HLA class II elements are involved in this recognition process in a single individual. This demonstrates that T cells that are present and activated at the site of a human autoimmune disease may show considerable heterogeneity in their recognition of autoantigen on the target tissue. This contrasts with the limited heterogeneity recently reported in some animal models and has potentially important implications for both our understanding of the autoimmune process in humans and the design of immunotherapies to reverse it.